40 HADITS PEDOMAN NU KARYA KH. HASYIM ASY’ARI Studi Takhrij dan Analisis Konteks Sosial Keagamaan Berdirinya NU - Hasan Su’aidi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This study seeks to uncover the quality of 40 hadith on NU foundations, religious and social background for its writing and selection and themes classification contained in book Arba’ina Haditsan Tata’allaqu bi Mabadi’i Nahdlat al-Ulama’. This study revealed that the quality of the hadith is varied between shaheeh, hasan and dhaif. The theme range of da'wah / commanding the good and forbidding the evil, leadership, worship, must follow the Sunnah, morality and unity. While religious social context influenced by the global and local situation.